Aksesibiltas dan Partisipasi Politik Penyandang Disabilitas di Kabupaten Jember - Asrorul Mais; Lailil Aflahkul Yaum (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to describe 1) regulations related to election implementation for disability, 2) constraints in realizing election access for peoples with disabilities, 3) efforts to realize election access for peoples with disabilities and 4) the role of peoples with disabilities to participate in politics. The method in this research uses descriptive qualitative. The results of the study indicate that the election law and peoples with disabilities have accommodated the rights of persons with disabilities in politics. While the obstacles are structural and cultural constraints from the government, the society and people with disabilities. As for the efforts made by the Jember Ellection Committee to realize elections access is to build communication with disability organizations and form democratic volunteers from the disability segment. Peoples with disabilities both personally and in organizations actively carry out the discourse and provide advice to the government and Jember Ellection Committee for the realization to improve electoral access. From the results of the study it can be concluded that in accordance with the Election Law on disability the KPU continues to make efforts to include persons with disabilities in elections to reduce and disability to vote. Keywords: Accessibility, Participation, Politics, Disability